Dinâmica dos movimentos sociais no processo de regularização fundiária urbana no município de Ferreira Gomes – AP - ALMEIDA, Elielson Rabelo (2022)
The municipality of Ferreira Gomes - AP, carries out from 2019 through Municipal Law 320, the Urban Land Regularization Program, called “Regulariza Ferreira”, which is based on regularizing urban lots in that municipality. This article sought to understand the dynamics of participation of Ferreira Gomes' social movements in the urban land regularization process promoted by the municipality. Based on authors such as Alonso (2009), social movements defined here are based on the theory of political confrontation, therefore, bodies such as municipal councils, churches, associations, street movements and, naturally, grassroots movements with a specific cause. In addition to research in texts, articles, books and documents. Fieldwork was carried out through semi-structured interviews with representatives of social movements that work in Ferreira Gomes in different segments, and also with representatives of municipal government secretariats. The question that guided this work was: do Ferreira Gomes' Social Movements participate in the municipality's urban land regularization policy? Society has no or no participation in the creation and implementation of this policy, given that social mobilization for events organized by the city hall is carried out through digital/social media, that is, the city hall activates the leaders so that they can disseminate the information. Therefore, there is no strong social participation, neither on the part of social movements, nor on the part of other municipal government bodies. The program works in isolation, with the purpose of subdividing urban land, having as an outcome, the delivery of the definitive title.